Pengaruh Corporate Governance Terhadap Profitabilitas Bank Umum Syariah Indonesia Periode 2018-2021 - Rafiuddin, Muhammad; Wakhid Musthofa, Muhammad (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2023)
Corporate governance is a important key to improve the performance of Islamic commercial banks. This research aims to determine the influence of corporate governance as measured by the board of director, shariah supervisor board, board of commissioner on the profitability in Indonesia Shariah Commercial Bank from 2018-2021. Uses a panel data approach with multiple linier regression analysis where the sample is collected from 7 Indonesia Shariah Commercial Banks with 112 of total data in quarterly. The result of this study found that Shariah Supervisor Board has a negative significate effect and Commissioner Board has a positive significant effect on profitability. Meanwhile board of director has no significant effect on profitability shariah commercial banks. Furthermore, these findings shall be consideration for managers in making policies.